EDUKASI PEMANFAATAN SOSIAL MEDIA : MENINGKATKAN MOTIVASI DAN LITERASI BAHASA INGGRIS SISWA MELALUI APLIKASI TIKTOK - Afrillia Anggreni (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
Low motivation tends to make students passive, indifferent, bored, and even frustrated in the learning process. As a result, they cannot maximally achieve their learning goals. This was what students at SMP Negeri 1 Atap Lik Layana Indah Palu experienced, as seen from the large number of students who were not focused when the teacher was teaching in class, lack interest in reading when given independent learning assignments, and appear bored during the learning process. The main factors causing this were a lack of human resources, facilities, and infrastructure, which result in monotonous and uninteresting learning methods or approaches. Therefore, more enjoyable, interactive and innovative activities are needed to create a good learning environment to increase motivation and stimulate students' interest in reading. The activity is the use of creative TikTok content. The applied method in this activity is training in which students are taught to utilize creative TikTok content in the form of reading challenges and English conversations assisted by the TikTok duet feature, as well as introducing short context-based story videos. The results of this activity point out that the students have responded positively. Through this activity, students' motivation, literacy skills, and English proficiency can improve